(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Back ground: Hip fractures are breaks in the neck and intertrochanteric region. These are serious injuries that most often occur in elderly persons and create a major social, psychological, economical and public health problem in this old age. Most hip fractures require surgery, hospitalization, and extended rehabilitation. This puts lot of economical and social burden on the public and government sectors. Objectives: To assess the risk factors of hip fractures among the patients of all age groups presenting for cognitive assistance. Methods: This study was conducted among the patients admitted in Orthopaedic Department of Sheikh Zayed Medical College Rahim Yar khan. All the patients regardless of age, sex and educational level admitted with hip fractures during the period of January 2013 to December 2013 were included in the study. Results: There were 133 patients admitted with hip injuries. Among these 133 patients that were admitted with hip fractures, there were 45(33.8%) female and 88(66.2%) male, the mean age of the patients was 50.64 years and the Standard Deviation was 19.94 years. The lower limit of age was 3 years and upper limit was 100 years. The majority of the patients 63.91% were in between the age group of 40 to 80 years. Conclusion: The hip fractures increases as the age advances. This temporal rise can be reduced with nutritional supplements for the prevention of osteoporosis. The prevention of osteoporoses will reduce the hip fractures that will ultimately alleviate the disability and burden of the disease. Key Words: Hip fracture, elderly persons, health problem